Humic acid, biochar‐based microbial agent and vermicompost improve cotton growth, photosynthesis, yield and fiber quality in saline‐alkali soil - Li, Ge; Shan, Yuyang; Bai, Yungang; Nie, Weibo; Sun, Yan; Su, Lijun; Zhang, Jianghui; Liu, Hongbo; Ding, Yu; Wang, Xiaoyan; Lu, Hongqin; Ye, Jinhao; et al. (Journal of the science of food and agriculture, 2025)
Humic acid (HA), biochar-based microbial agent (M) and vermicompost (V) have been shown to improve soil structure and increase crop yields. However, the combined effects of these amendments on cotton growth, photosynthetic characteristics, yield and fiber quality in saline-alkali soils remain unclear. The results obtained in the present study showed that: (i) compared to the control (CK), the single and combined applications of HA, M and V increased soil water storage and reduced soil salinity; (ii) the combined application of HA, M and V resulted in the greatest improvements in plant height, stem diameter, leaf area index, net photosynthetic rate, stomatal conductance, intercellular CO concentration, transpiration rate, SPAD, biomass and yield, with increases of 39.2%, 36.0%, 88.1%, 43.9%, 97.8%, 41.1%, 133.9%, 18.0%, 85.1% and 31.8%, respectively; (iii) the optimal application rates of HA, M and V were 120, 60 and 120 kg ha , respectively; (iv) correlation analysis and structural equation modeling revealed that cotton yield was positively correlated with biomass, growth indices and photosynthetic characteristics, whereas fiber quality was positively correlated with photosynthetic characteristics, soil water storage and yield. Based on these findings, the combined application of HA, M and V is recommended to enhance cotton growth in saline-alkali soils. © 2025 Society of Chemical Industry.